Fungal Infection Exacerbate Nasal Polyposis: A study conducted at KGN Teaching Hospital Bannu-KPK. - Mohammad Iqbal; Sahibzada Fawad Khan; Sohail Khan; Wasim Ahmad (International Journal of Endorsing Health Science Research, 2021)
Background: Nasal polyps were believed to be small tumours of nasal or sinus mucosa. With progressing research, they are associated with enlargement or swelling of nasal or sinus mucosa, allergy, asthma, any infection, sensitivity to aspirin, and/or cystic fibrosis unclear etiology. The present study aims to evaluate the prevalence of fungal infections that can result in the onset of nasal polyposis in the residents of district Bannu, Pakistan.